REASONS WHY MARRIED WOMEN DO NOT PAP SMEAR: A STUDY OF FEMALE TEACHERS AT STATE JUNIOR HIGH SCHOOL 20, NORTH PONTIANAK, WEST KALIMANTAN - Candra, Dewi; Titihalawa, Elly Marce; Goretik, Maria; Kurniasih, Dwi (UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: Pap smear is an early detection of cervical cancer caused by the HPV virus with more accuracy. The cause of the high incidence of cervical cancer is due to the level of awareness of women who do not want to do a Pap smear. Objective: To understand the various factors that influence the decision of married women who do not Pap smear at SMPN 20 Pontianak Utara, West Kalimantan. Method: This study is qualitative with a case study approach. This method was chosen to focus attention on a case intensively and in detail, namely 5 informants who are married but do not do a Pap smear. Results: Some of the reasons why married women never do a Pap smear are trauma from their past, fear of the examination, feeling healthy and not feeling the need to do the examination, not being familiar with the examination process, fear and shame, no support or invitation from the environment to do the examination, expensive costs, feeling ashamed and afraid especially if the examiner is a male doctor, lack of knowledge about the Pap smear procedure, not knowing the examination process, location, and costs required. Conclusion: Pap smear examination for married women is a must for personal health. Pap Smear examination requires support from close relatives, the daily residential environment and workplace, especially among married women.